2019
DOI: 10.1002/ccr3.2601
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasospasm induced by cisplatin for seminoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractVascular toxicity is one of serious complications following cisplatin-based chemotherapy. This case suggests that cisplatin has a potential risk of delayed occurrence of vasospastic angina. It is important to perform careful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It was observed that intima-media thickness is higher than the estimated value for age, confirming that cisplatin triggers a degenerative process of the vessel walls, leading to occlusive vascular disease in the long term [ 62 ]. Moreover, cisplatin has the potential risk of delayed onset of vasospastic angina [ 63 ].…”
Section: Platinum Compounds (Cisplatin)mentioning
confidence: 99%
“…It was observed that intima-media thickness is higher than the estimated value for age, confirming that cisplatin triggers a degenerative process of the vessel walls, leading to occlusive vascular disease in the long term [ 62 ]. Moreover, cisplatin has the potential risk of delayed onset of vasospastic angina [ 63 ].…”
Section: Platinum Compounds (Cisplatin)mentioning
confidence: 99%
“…There are few reports of MI with troponin measurements and documented coronary angiography following cisplatin administration. These reports attributed the ischemic event to CAS [ 82 , 83 , 84 , 85 , 86 ]. Troponin elevation was inconsistently present, but coronary angiography recurrently showed no significant CAD, consistent with MINOCA.…”
Section: Etiology and Mechanisms Of Myocardial Infarction In Cancer P...mentioning
confidence: 99%
“…Troponin elevation was inconsistently present, but coronary angiography recurrently showed no significant CAD, consistent with MINOCA. Notably, one report documented that acetylcholine provocation induced severe coronary vasospasm associated with chest pain and significant ST elevation [ 82 ]. Cisplatin-induced MINOCA via CAS may occur early during the treatment regimen or delayed for years after completing cisplatin treatment [ 82 ].…”
Section: Etiology and Mechanisms Of Myocardial Infarction In Cancer P...mentioning
confidence: 99%
See 1 more Smart Citation